Perancangan User Interface/Experience Aplikasi Penyewaan Motor Listrik Online XYZ Menggunakan Metode Kansei Engineering - Salim, Rizki Irawan Salas; Sodik, Anwar (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2025)
This study aims to redesign the interface (UI) and user experience (UX) of the XYZ application with the Kansei Engineering approach to capture the emotional needs of users and translate them into design elements. The research process was carried out through initial usability testing using the System Usability Scale (SUS) method, followed by Kansei word identification, semantic differential questionnaire preparation, and multivariate statistical analysis (CCA, PCA, FA, and PLS). The resulting design draft was then retested using the SUS method. The results showed that the SUS score decreased from 61.25 to 60.13. This decrease indicates that although the Kansei Engineering approach can help compile designs based on user emotional perceptions, the implementation of the design still requires further evaluation to be functionally and emotionally aligned.